2001
DOI: 10.1016/s0002-9440(10)63032-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic Analysis of the TCR-Vβ Repertoire in 98 Persistent Expansions of CD3+/TCR-αβ+ Large Granular Lymphocytes

Abstract: At present, a major challenge in the initial diagnosis of leukemia of large granular lymphocytes (LGLs) is to establish the clonal nature of the expanded population. In the present study we have analyzed by flow cytometry immunophenotyping the TCR-Vbeta repertoire of 98 consecutive cases of persistent expansions of CD4(+) or CD8(+bright) CD3(+)/TCR-alphabeta(+) LGLs and compared the results with those obtained in molecular studies of TCR-beta gene rearrangements. Fifty-eight cases were considered to be monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(28 citation statements)
references
References 45 publications
2
24
0
2
Order By: Relevance
“…In contrast to B-cell lymphoid proliferations, in which flow cytometric analysis of immunoglobulins for light chain restriction can determine clonality, neoplasia cannot be determined easily by flow cytometry analysis of T-cell or NK cell proliferations. This may change, however, with the advent of the development of antibodies to the family of T-cell antigen receptor beta chains (31,32). Large panels of monoclonal antibodies to the TCR-V␤ repertoire can detect expansion of one or more TCR-V␤ families and can predict clonality in some instances (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to B-cell lymphoid proliferations, in which flow cytometric analysis of immunoglobulins for light chain restriction can determine clonality, neoplasia cannot be determined easily by flow cytometry analysis of T-cell or NK cell proliferations. This may change, however, with the advent of the development of antibodies to the family of T-cell antigen receptor beta chains (31,32). Large panels of monoclonal antibodies to the TCR-V␤ repertoire can detect expansion of one or more TCR-V␤ families and can predict clonality in some instances (32).…”
Section: Discussionmentioning
confidence: 99%
“…This may change, however, with the advent of the development of antibodies to the family of T-cell antigen receptor beta chains (31,32). Large panels of monoclonal antibodies to the TCR-V␤ repertoire can detect expansion of one or more TCR-V␤ families and can predict clonality in some instances (32). However, the large panel is unwieldy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that LGL proliferations arise as a consequence of chronic immune stimulation [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…of these cases [2,12,13]. Unlike evaluation of T-cell LGL proliferations, in which clonality can be assessed with molecular analysis of the TCR genes and TCR variable region repertoire studies [9], assessment of clonality remains a challenge in NK cell disorders. Thus demonstration of an aberrant immunophenotype may be of a great help in the detection of clonal expansion of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies are available for more than 80% of the variable region families of the β chain (Vβ). TCR Vβ antibody studies can be used as an initial screening method for the detection of unbalanced use of β chain gene families [25,26].…”
Section: Diagnosismentioning
confidence: 99%